Differences in migration phenology of warblers at two stopover sites in eastern Russia suggest a longitudinal migration pattern - Bozó László; Anisimov Yury; Heim Wieland (KEAI PUBLISHING LTD, 2025)
Long-distance migratory birds often face major geographical barriers on their journey. While some species are able to cross them, others use longer routes to avoid such barriers. Little is known about the strategies of Siberian landbird migrants, which either cross or circumvent the deserts and mountain ranges of Central Asia en route to their non-breeding sites in Southeast Asia. Here we compare data on migration phenology and morphology from two bird ringing stations in eastern Russia, situated at similar latitudes but with a longitudinal difference of 1500 km, to hypothesise migration patterns. We found significant differences in timing between the two sites (birds migrated significantly earlier in spring and significantly later in autumn in the east), suggesting longitudinal migration as a result of migration detour. However, morphological differences show a less clear pattern. We argue that most Siberian landbirds might opt for a detour through the Russian Far East instead of a direct route in order to avoid unfavourable stop-over habitat in Central Asia. However, tracking studies will be necessary to prove this.